2005
DOI: 10.3354/dao064091
|View full text |Cite
|
Sign up to set email alerts
|

Taura syndrome virus from Belize represents a unique variant

Abstract: A Taura syndrome virus (TSV) isolate from cultured Penaeus vannamei grown in Belize, Central America was characterized and shown to be a unique isolate. Mortality rates in laboratory infections of specific pathogen-free (SPF) P. vannamei, reactivity of the virus with monoclonal antibody (MAb) 1A1 and phylogenetic analysis demonstrated that the Belize isolate (BLZ02TSV) is a new variant of TSV. The Hawaiian 1994 TSV isolate (HI94TSV, GenBank AF277675) was used as the reference isolate for these studies. Laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…1C). Our results were also consistent with Bz01 being more virulent than UsHi94 (Erickson et al 2005. The data in Fig.…”
Section: Survival and Lesions In Tsv-resistant Litopenaeus Vannamei Asupporting
confidence: 82%
See 1 more Smart Citation
“…1C). Our results were also consistent with Bz01 being more virulent than UsHi94 (Erickson et al 2005. The data in Fig.…”
Section: Survival and Lesions In Tsv-resistant Litopenaeus Vannamei Asupporting
confidence: 82%
“…For instance, Erickson et al (2005) demonstrated that Pacific white shrimp Litopenaeus vannamei (also called Penaeus vannamei) (Farfante & Kensley 1997) experimentally infected with a Belize isolate (Bz02) showed higher mortality than they did when infected with a Hawaiian isolate (UsHi94) (referred to as BLZ02TSV and Hi94TSV, respectively, in the cited paper). Phylogenetic analysis revealed that Bz02 was distinct among 29 isolates of TSV, despite the fact that TSV displays low genetic variation from 0 to 5.6% in nucleotide sequence and from 0 to 7% in deduced amino acid sequence ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous challenge tests at UA-APL, the final survival of the SPF line infected with TSV HW 94 was about 20-30% (Tang et al, 2004;Erickson et al, 2005;Srisuvan et al, 2006). However, in recent TSV challenge tests, including the one presented here, final survivals have been lower.…”
Section: New Tsv Isolatementioning
confidence: 55%
“…2 as 'HI94TSV.' The references listed with the GenBank accession numbers for the sequence information for 'Hawaiian' and 'French' TSV isolates used by the authors in their analysis clearly indicate that AF510518 (Erickson et al 2005) is a 1164 bp portion of the TSV VP1. This sequence is 100% identical to the sequence for VP1 within the entire TSV genome sequence given by Mari et al (2002) in AF277675.…”
Section: Tsv In Penaeus Vannamei Cultured In France?mentioning
confidence: 95%